Trichotillomania in a Case of Vascular Dementia - De Sousa, Avinash (Medknow Publications & Media Pvt Ltd, 2013)
Trichotillomania is a complex psychiatric disorder and occurs along with a large number of comorbidity. We report a case of trichotillomania associated with vascular dementia. Trichotillomania in our case did not resolve using mirtazapine or conventional medications. Trichotillomania in dementia seems to have a neurobiological origin that needs to be elucidated.